Molecular detection of Theileria and Babesia infections in cattle - Altay, Kursat; Aydin, M. Fatih; Dumanli, Nazir; Aktas, Munir (Elsevier, 2008)
This study was carried out to determine the presence and distribution of tick-borne haemoprotozoan parasites (Theileria and Babesia) in apparently healthy cattle in the East Black Sea Region of Turkey. A total of 389 blood samples were collected from the animals of various ages in six provinces in the region. Prevalence of infection was determined by reverse line blot (RLB) assay. The hypervariable V4 region of the 18S ribosomal RNA (rRNA) gene was amplified with a set of primers for members of the genera Theileria and Babesia. Amplified PCR products were hybridized onto a membrane to which generic- and species-specific oligonucleotide probes were covalently linked. RLB hybridization identified infection in 16.19% of the samples. Blood smears were also examined microscopically for Theileria and/or Babesia spp. and 5.14% were positive. All samples shown to be positive by microscopy also tested positive with RLB assay. Two Theileria (T annulata and 7: buffelilorientatis) and three Babesia (B. bigemina, B. major and Babesia sp.) species or genotypes were identified in the region. Babesia sp. genotype shared 99% similarity with the previously reported sequences of Babesia sp. Kashi 1, Babesia sp. Kashi 2 and Babesia sp. Kayseri 1. The most frequently found species was 7: buffeli/orientalis, present in 11.56% of the samples. T. annulata was identified in five samples (1.28%). Babesia infections were less frequently detected: B. bigemina was found in three samples (0.77%), B. major in two samples (0.51%) and Babesia sp. in five samples (1.28%). A single animal infected with T. buffeli/orientalis was also infected with B. bigemina. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Theileria; Babesia; PCR; Reverse line blot; Cattle; Turkey